OsTZF1, a CCCH-tandem zinc finger protein gene, driven under own promoter produces no pleiotropic effects and confers salt and drought tolerance in rice. (31st December 2022) - Ilyas, Muhammad; Hussain Shah, Safdar; Fujita, Yasunari; Maruyama, Kyonoshin; Nakashima, Kazuo; Yamaguchi-Shinozaki, Kazuko; Jan, Asad
ABSTRACT: Different abiotic stresses induce OsTZF1, a tandem CCCH-type zinc finger domain gene, in rice. Here, we report that transgenic rice plants overexpressing OsTZF1 under own promoter ( POsTZF1 :OsTZF1- OX [for overexpression]) transferred to soil showed normal growth similar to vector control plants. The POsTZF1 :OsTZF1- OX produced normal leaves without any lesion mimic phenotype and exhibited normal seed setting. The POsTZF1 :OsTZF1- OX plants showed significantly increased tolerance to salt and drought stresses and enhanced post stress recovery. Microarray analysis revealed a total of 846 genes up-regulated and 360 genes down-regulated in POsTZF1 :OsTZF1- OX salt-treated plants. Microarray analysis of POsTZF1: OsTZF1- OX plants showed the regulation of many abiotic stress tolerance genes. These results suggest that OsTZF1 -OX under own promoter show abiotic stress tolerance and produces no pleiotropic effect on phenotype of transgenic rice plant.